Perceived Value of Online Reviews, Trust, Risk Perception, Purchase Intention and Actual Purchase - Sembiring, Timothy Hudson; Nisa, Puspita Chairun (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The development of technology today greatly affects the stability of the economy, especially in Indonesia. All types of buying and selling activities that are usually done directly with the seller, now we can easily shop online using only a smartphone. Shopee is one of the growing e-commerce in Indonesia. Shopee creates a safe, fun, and easy shopping experience for consumers, because there are positive online reviews that can motivate consumers to trust a brand. This study aims to explore the empirical understanding of the effect of perceived value in online reviews, trust, and risk perception on purchase intention and analyze the impact of purchase intention on actual purchases. The population taken in this study is the Bekasi community. The selected sample amounted to 100 with the criteria of customers who use shopee e-commerce, male and female, with the age of the respondent between 18 and 60 years old who made at least one online purchase during the last month at shopee. The analysis method used is Partial Least Square Structural Equation Modeling. The results of the study state that the perceived value of online reviews, trust, perceived risk can increase online purchase intentions have a positive effect on actual purchases. Future research is expected to expand the range of regions and add other variables related to actual purchases such as product quality. Keywords: Actual Purchase, Online Purchase Intention, Perceived Risk, Perceived Value of Online Reviews, Trust